Hungary: No Euro Until ‘Maastricht 2.0 Criteria’ Are Met - Marinkás, György (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
The first part of the current chapter introduces Hungary’s convergence data through convergence reports from years that the author deems milestones and, based on the relevant scientific literature, tries to answer why the Hungarian Central Bank took a cautious approach to the country’s accession to the Eurozone and why academic literature adopted the ‘real convergence’ thesis as a basic principle. The second part introduces the constitutional and statutory framework of the Hungarian Central Bank’s aims, functioning, and structure and presents certain academic debates on the chosen regulation. The third part of the book introduces the Hungarian Central Bank’s monetary policy for crisis management in two parts: crisis management tools aimed at tackling the Euro crisis and tools aimed at mitigating the negative economic effects of the COVID-19 pandemic and the Russo-Ukrainian War. While tackling the first two crises required unconventional tools, such as near-zero interest rates and active refinancing, the latter required a return to old-school restrictive monetary policy, with high base rates and the phasing out of refinancing tools.Keywords: Hungarian Central Bank, monetary policy, convergence criteria, real convergence, Maastricht 2.0., Economic and Monetary Union, Eurozone, Banking Union, COVID-19, Russo-Ukrainian War